Design an online shopping website with virtual fitting room - Zhang, Xinyue (2019)
With the rapid development of Internet, people gradually choose to shopping online instead of traditional window shopping. Meanwhile, the biggest problem of online shopping is that customers will get unsatisfied products of higher probability compared with traditional window shopping, without touching and trying on the items, especially for sunglasses. Although the facial detection technologies are developed in recent years, the ecommerce websites still don’t use it widely. Mobile devices are increasingly developed, with various screen resolutions. A website need to be user-friendly which includes readable text without requiring zoom, adequate space for tap targets and no horizontal scrolling. To make sure a website offers an optimized browsing experience for different mobile devices, Responsive web design (RWD) provides a fluid and flexible layout which could automatically adjust according to different screen resolutions. The purpose of the final year project is to implement a responsive ecommerce website with the feature of virtual try on